Pengaruh Corporate Culture dan Leadership Terhadap Employee Engagement BPJS Ketenagakerjaan - Asti Rifiana; Yanuar Luqman; Zainiyah Alfirdaus (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2022)
This study aims to determine the effect of corporate culture and leadership style on employee engagement. Corporate culture is measured by 4 dimensions, namely adaptability, consistency, involvement, and mission. Leadership is measured using 4 dimensions, namely ideal influence, inspirational motivation, intellectual stimulation, and individual attention. Employee engagement is measured by 4 dimensions, namely leadership style, remuneration, skill development, and work environment. This type of research is quantitative through an explanatory approach. This study used primary data using questionnaires and obtains a sample of 350 employees. Hypothesis testing is used multiple linear regression with SPSS. Based on hypothesis testing, this study concludes that corporate culture and leadership have a significant positive effect on employee engagement.